171 The Effect of Collagenase Clostridium Histolyticum Injection on the Treatment Patterns of Peyronie's Disease: An Analysis of Large Health Care System Over 15-year Period. Issue 1 (1st April 2022) - Mirheydar, H.; Hsieh, T.; Krug, A.; Aleman, M.
ABSTRACT: Introduction: Penile plication or excision with grafting has traditionally been the only effective treatment for stable Peyronie's disease (PD) without concurrent erectile dysfunction. Intralesional collagenase clostridium histolyticum (CCH) was approved by the U.S. Food and Drug Administration(FDA) in 2013 for patients with stable disease with curvature between 30 and 90°. The effect of CCH injection therapy on the diagnosis and treatment patterns of PD is unknown. Objective: We studied the effect of FDA approval of CCH on the management of PD in a population-based analysis. We analyzed the effect of the advent of CCH on rates of prescribing of oral treatments, including vitamin E, colchicine, and pentoxifylline along with surgical intervention. We also studied the effect of injection therapy on the rate of new diagnosis of PD in a population-based analysis. Methods: The Kaiser Permanente Southern California database, which provides comprehensive data on all Kaiser Permanente patients in 15 medical centers in the Southern California region was reviewed. Patients undergoing a penile prosthetic surgery for concurrent erectile dysfunction were excluded. PD patients were identified using ICD-9 code and ICD-10 code. Injection therapy was determined using CPT codes, as well as the use of CCH based on the pharmacy database. Surgical therapy (either penile plication or excision with grafting) was identified using CPT codes. The use of oral medication treatment (e.g., vitamin E, colchicine, and pentoxifylline) was ascertained using both the outpatient and inpatient pharmacy database. Main Outcome Measure This study first presented the annual incident rates of PD from 2004 to 2020 among Kaiser members ages 18 or older, and, among eligible PD patients, the annual rates of receiving CCH injection therapy, surgical therapy, and oral medication treatment. Descriptive statistics and multivariable logistic regression modeling were used to assess factors influencing the choice of intralesional injection vs surgical therapy. Results: From 2004 to 2020, 11, 706 patients presented for PD management (average incident rate, 52.8 per 100, 000 eligible members). Median age was 58 years and 54.5% were Caucasian. Over the study period, the incident rate (per 1, 000 eligible patients) of surgical management declined on average by 0.37 each year (p < 0.001) while there was an increase of 0.43 for injection therapy (p < 0.001). Following the FDA's approval of CCH in 2013, the average incident rate (per 1, 000 eligible patients) for surgical therapy in 2014-2020 declined by 2.8 (p < 0.001) compared to that in 2004-2013, whereas it significantly increased by 5.1 (p < 0.001) for injection therapy. Average rates of prescribing of oral colchicine and vitamin E significantly decreased from 2016-2020 compared to 2004-2015 (p<0.001), while average rates of prescribing pentoxifylline significantly increased (p<0.001). Patients presenting in the post-CCH era were approximately two times significantly more likely to receive injection therapy (OR: 2.08; P < 0.001 CI: 1.47 to 2.94). On multivariable modeling, patients more likely to receive injection therapy as primary treatment for PD were ages 45-54 (OR: 2.77; P = 0.002; CI: 1.34 to 5.73). Conclusions: Since the Introduction: of CCH, there has been a significant change in the management pattern for PD (decrease in surgical therapy, and increase in intralesional injections). Since the recent publication of AUA Guidelines on PD in 2015, there has been a significant decrease in non-evidence supported oral medication prescriptions. Disclosure: No